OPTIMUM OVERCURRENT RELAY COORDINATION: A REVIEW - Raza, S. A.; Mahmood, T.; A. Bukhari, S. B. (The Nucleus, 2014)
In power system the protective relays are coordinated optimally to ensure that only the faulted zone of the system will be detached when the abnormal operating state will occur. The interconnected system as well as deregulated environment and increase in user demand force the utilities to implement optimally coordinated protection scheme to increase reliability of the system. In this paper an overview of overcurrent relay coordination techniques is presented. Deterministic, heuristic, hybrid and trial and error optimization techniques, have been reviewed to understand their method of implementation, modes of operation, nature of power distribution system, advantages and disadvantages.